Aproximações entre o Serviço Social do Reino Unido e do Brasil na contestação ao Serviço Social Tradicional (2024)
This article presents some parallels between Social Work in Brazil and the United Kingdom - especially regarding the rebuttal of Traditional Social Work. To this end, this article engages with the main literature that discusses the historical determinants contributing to the emergence of the contestatory perspective of Traditional Social Work in the two countries, within the context of capitalist social relations between the 1970s and 1990s, highlighting the theoretical-methodological, technical-operational, and ethical-political aspects. It is concluded that the dialogue between the critical strands of Social Work in both countries is promising and, therefore, deserves to be enhanced.